Deleuze and Absolute Immanence: Achieving Fully Immanent Inquiry. (June 2021) - Hein, Serge F.
The concepts of immanence and transcendence have a long and varied history in philosophy. In an ontology of absolute immanence, immanence is not dependent on something else. Immanence is immanent only to itself, with the result that all transcendence is eliminated. Deleuze, like Derrida and Foucault, has an unwavering commitment to absolute immanence, which he conceives of in different ways during his career. There is both a logical and an ethical problem with any ontology of transcendence, and an ontology of absolute immanence addresses both these problems. Fully immanent inquiry rejects all forms of methodological transcendence. It avoids relying on the authority of any existing qualitative (or other) methodological structures such as paradigms, methodologies, methodological concepts, methodological techniques, and methodological practices. It also avoids all binary opposites and universals and fosters experimentation and creation of the new. An example of fully immanent research is also discussed.